Electrocatalytic oxygen evolution reaction for energy conversion and storage: A comprehensive review - Tahir, Muhammad; Pan, Lun; Idrees, Faryal; Zhang, Xiangwen; Wang, Li; Zou, Ji-Jun; Wang, Zhong Lin (Nano energy, 2017)
Water oxidation or oxygen evolution reaction (OER) electrocatalysis got much attention in the last few years because of its prime role in water splitting, rechargeable metal-air batteries and fuel cells. Therefore, the development of efficient, abundant and economical catalysts for water oxidation reaction is one of the main subjects of present study in renewable energies. This review article summarizes the very recent efforts in the field of OER electrocatalysis along with the faced challenges. The solutions to these challenges also outline with appropriate examples of scientific literatures. Significantly, the present review will provide the standards to evaluate the activity and stability for heterogeneous OER catalysts. It will clearly summarize the future directions and applications, especially the combination of sustainable energy utilization (like triboelectric nanogenerator) with water splitting. The providing study will help to explore and develop better catalysts and units for practical applications and will offer basic understanding of OER process along with the standard parameters to evaluate the performance. [Display omitted] •The recent efforts in water oxidation electrocatalysis were reviewed.•The standard parameters to evaluate the performance were emphasized.•This review also provides the future direction and application.